Baseline of the sexual and reproductive health project for adolescents in Medellín: the qualitative component - Nancy E. Gallo R (Universidad de Antioquia, 2009)
Objective: To approach the perception of adolescents and adults opinion makers on teenage pregnancy, sexual and reproductive health (s r h), use of birth control (b c) and use of s r h services. Methodology: a descriptive study ethnographic with focused interviews and semi-structured guide. The convenience sample consisted of 80 young people (men and women) between 14 and 19 years old and 6 adult women opinion makers. Eight focus groups were conducted with youth and six interviews. Results:in intergenerational encounters are explanatory reasons on teenage pregnancy in the city of Medellin The construction of the process of trust-distrust in the conquest and the adolescent partner life affects the use of b c, including the condom. The main barrier to adolescents' access to s r h services is the lack of credibility in them. Conclusions: The break with the ideal of the adult world, the ideas they have about love, relationships, cultural precepts that designate the gender behavior and credibility they have about s r h services are fields of analysis that are directly linked to the issue of teenage pregnancy in the city of Medellin.